The effect of Smash training using hanging balls on the accuracy of Open Smash - Putri, S. A. R.; Dlis, F.; Samsudin; Fajar, M.; Wanto, S.; Sari, P. S. (International Journal of Human Movement and Sports Sciences, 2021)
The purpose of this study was to determine the effect of smash practice using a hanging ball on the accuracy of open volleyball smash games. This research method is to use an experimental research design. The research sample consisted of 60 male volleyball players. The sample was divided into two groups, namely the experimental group and the control group with the matching ordinary pairing technique. The research instrument was the APHEER test smash skills. The data analysis technique used the t-test to see the effectiveness of increasing the training given to the sample, processing data analysis with the SPSS version 23 software program. The results showed that the average accuracy of the smash of male volleyball players who participated in extracurricular activities was the pretest group results, control of 6.83 and posttest control group of 5.65 which means there is no significant increase. Then for the results of the research group that was given exercise, the pretest score of 6.77 and posttest the experimental group was 10.63. Based on the research data, there was a significant increase in the smash results in the experimental group. The conclusion of this research is that there is an effect of smash practice using a hanging ball on the accuracy of open volleyball smashes. The results of this study provide a contribution for coaches and volleyball players to improve smash skills, especially increasing the accuracy of open smashes.